Antigen-antibody Interactions in vitro: Systematic Analyses of Tests for Antibodies to Viruses Reveal Their Reaction Lines and Open the Way for Gold and Reference Standard Assays and Adequate Routine Tests - Viggo Bitsch (Microbiology and Biotechnology Research: An Overview Vol. 3, 2025)
Antibodies can be detected within a few days after infection. Antibodies can be divided into two groups, i.e., 1) neutralising antibodies that are capable of inactivating viruses in vitro by being bound to their antigenic neutralisation determinant on the virion and 2) non-neutralising antibodies which are unable to neutralise the virus simply by being attached to their antigenic determinant. Interactions between antibodies and viruses are diverse and function in different ways in tests demonstrating the virus or antibody. Three antibody tests based on three different neutralisation reactions by antibodies and another two ELISA modifications, one showing a binding reaction and the other a blocking reaction by antibodies to be demonstrated, represent five different antigen-antibody interactions used for demonstrating antibodies to viruses. These five tests are: 1) the first-order virus neutralisation test, 2) the virus aggregation neutralisation test, 3) the complement-enriched virus neutralisation test, 4) the conventional antibody ELISA, and 5) the blocking antibody ELISA. Basic versions of these tests are evaluated. The reaction in each test is described. The reacting antibodies in the highest concentration, measuring the antibody titer and the test sensitivity, are, where relevant, defined as either neutralising or non-neutralising, and modifications adjusted to possess an appropriately high sensitivity are evaluated for routine use and for the potential application as a reference or even gold standard assay, cf. Definitions. The reaction in a first-order virus neutralisation test is slowly progressing and enduring, with increasing reaction periods, and the reacting antibodies are exclusively neutralising. The sensitivity of this test is both variable and adjustable. The test sensitivity is temperature-dependent and directly proportional to the reaction time. The very sensitive 37oC/24h configuration (reaction at 37oC for 24 hours) is concluded to be the ideal reference and gold standard assay measuring neutralising antibodies to viruses. In the virus aggregation neutralisation test, the inactivation of the virus by aggregation is prompt and short-lasting. All antibodies to the various antigenic determinants on the virus, neutralising or non-neutralising, react synergistically. The reaction depends strongly on the antibody concentration. The test sensitivity is rather low and practically not adjustable, because of which the test is unsuited for demonstrating antibodies to viruses. This test is almost identical to a conventional 37oC/1h neutralisation test, which by many has been considered to be a gold standard assay for demonstrating neutralising antibodies. In the complement-enriched neutralisation test, the reacting antibodies of the highest concentration are non-neutralising. The reaction is almost instantaneous immediately after the addition of complement due to a prompt reaction of the C1q component of complement with antigen-antibody complexes formed, but otherwise of first order with extended increasing reaction periods, following the first-order binding of non-neutralizing antibodies to the virus. The sensitivity of a 37oC/24h modification is high and for IgG antibodies equal to that of a conventional antibody ELISA with identical reaction conditions. However, it is laborious, because of which the latter will be a better alternative. The conventional antibody ELISA is basically a first-order assay, and the reacting antibodies of the highest concentration, determining the antibody titer and test sensitivity, are non-neutralising. Virus aggregation is impossible, and the sensitivity is directly proportional to the length of the reaction time. A 37oC/24h configuration will be the ideal reference and gold standard antibody assay for measuring titers of non-neutralising antibodies in the highest concentration and test sensitivities. The blocking antibody ELISA is in its basic form, simple, very sensitive, specific, and applicable for automation. It is well-suited for routine, large-scale examinations. The sensitivity of the blocking antibody ELISA depends on the reaction temperature and time, but the reaction is not of first order. Increasing the reaction time from 1 to 24 hours in a herpesvirus test raises the sensitivity by approximately a factor of 4. The reaction rate is decelerating with increasing reaction time, but still, the sensitivity is relatively high with extended reaction. With herpesviruses, the sensitivity of a 37oC/24h test is twice that of the 37oC/24h first-order neutralisation test, although 4 times lower than that of the conventional antibody ELISA. In its basic configuration, it is the test best suited for large-scale antibody examinations in diagnosing and controlling viral infections. The reactants can be varied to serve different objectives. The sensitivity and specificity of 37oC/24h modifications of the three antibody tests found of special value are regularly over 99 per cent when undiluted serum/plasma samples are examined. A particular subnormal level of antibodies associated with infection of young individuals having maternal antibodies capable of reducing the stimulus to antibody formation is described. This condition underlines that when the diagnosis of an earlier infection is decisive, e.g. in connection with control of herpesvirus infections in the veterinary medical field, a high test sensitivity is crucial. This study also addresses SARS-Cov-2 antibody testing.